Revisiting the Fama-French Framework with Contemporary Evidence from the Indonesian Stock Exchange - Misran, Alfian; Hamdani, Hamdani; Sutomo, Ibnu; Amiruddin, Amiruddin; Darmawati, Darmawati (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
This study revisits the size and value effects in emerging markets by re-examining the explanatory power of the Fama-French three-factor model in the Indonesian equity market. While previous studies have established the foundational role of firm size and book-to-market equity in developed markets, limited research has assessed their relevance in the evolving context of Indonesia’s capital market. Utilizing monthly data from non-financial firms listed on the Indonesia Stock Exchange (IDX) over the period 2015–2024, this study constructs 25 value-weighted portfolios sorted independently on size and book-to-market ratios. The Fama-French three-factor model is employed to analyse the impact of market risk premium, size (SMB), and value (HML) factors on stock returns. Our empirical analysis confirms that both the size (SMB) and value (HML) factors significantly contribute to explaining cross-sectional return variation, alongside the market risk premium. Notably, the size effect remains pronounced in small-cap firms, while the value premium is evident among firms with high book-to-market ratios. These findings corroborate results from other emerging markets such as India, Egypt, and China. Additionally, recent evidence from the Indonesian market, including the impact of bid-ask spread and return risk, as well as the performance of value stocks during the COVID-19 pandemic, further supports the continued relevance of firm characteristics in explaining asset pricing dynamics. The study reinforces the applicability of the Fama-French model in the Indonesian context, highlighting the significance of size and value factors in asset pricing. These insights are pertinent for both academic researchers and practitioners developing factor-based investment strategies in emerging markets.